Analisis Rasio Likuiditas Pada Perusahaan Sub sektor Perikanan Yang Terdaptar Di Bursa Efek Indonesia Pada Tahun 2016-2019 - Zulkarnaen, Dicky; Malahayati, Rina; Aramana, Desi (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2022)
This study aims to test the current ratio increases or decreases in fishery sub-sector companies listed on the Indonesian stock exchange (IDX) from 2016 - 2019 and the quick ratio increases or decreases in fisheries sub-sector companies listed on the Indonesian stock exchange (IDX) from 2016 – 2019. The research population is fishery sub-sector companies listed on the Indonesia Stock Exchange in 2016-2019. Analysis of the data used is quantitative and descriptive. The results of the study are the current ratio of the company PT Dharma Samudra Fishing Industries, Tbk in 2016 - 2017 decreased by 2.7% current debt is greater than current assets, the current ratio of the company PT Dharma Samudra Fishing Industries, Tbk in 2017 - 2019 decreased by 5 ,28% because current debt is greater than current assets, the company's current ratio of PT Dharma Samudra Fishing Industries, Tbk in 2018 - 2019 increased by 13.9% because current assets are greater than current debt.